Isolation and identification of Mycobacterium tuberculosis from patients that have relipase infection at Nasseriya province during 2004-2009 year - Qasim Hassan Awda'a (مجلة علوم ذي قار, 2019)
Mycobacterium tuberculosis that cause diease for  inhaled  and reach lungs , the disease  results  from  proliferation  at  organisms and  interactions  with the host, 3 months or years injected BCG  in the normal host, and there the production and development  of  lesions are caused by  healing  and multiplication  at the lung  or  progression  are  determined chiefly by the number of mycobacteria in the inoculum and their subsequent, and the Mycobacterium inter the host, tuberculosis is caused by Mycobacterium tuberculosis ,persons who have tuberculosis in their lungs can release tiny moulculos contain Mycobacterium tuberculosis  into the air by coughing , ,in 2004 a total of 200 patients (108 male and 92 femal),in 2005 a total of  67 patients (57 male  and 10 femal), in  2006 a total of  38 patients (29 male  and 9 femal ) , in 2007 a total of 28 patients (19 male 9 female ),in 2008 a total of 2 patients ( 2 male and non in female ),in 2009 a total of 67 patients (53 male  and 14 femal) , the males patints a total of 268 and  females patints a total of 134  the total  from 2004 to 2009  total of 402 patients , the aim  of  study  isolation  and  identification of Mycobacterium  tuberculosis from patients  that have  relipase infection  at Nasseriya province   during 2004-2009 year